2006
DOI: 10.1080/03008200600727756
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Cytodifferentiation in Mammalian Tooth Development

Abstract: The morphological stages of tooth development--bud, cap, bell, and terminal differentiation--have been known for decades. The past 10 years have seen the elucidation of many of the molecular events driving these morphogenetic stages. Signaling via the fibroblast growth factor (FGF), bone morphogenetic protein (BMP), hedgehog, and wingless protein families and their downstream transcription factors have been identified as key players in the epithelial-mesenchymal signaling loops driving tooth development. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 49 publications
1
55
0
4
Order By: Relevance
“…There has been much research on the molecular mechanisms responsible for initial odontogenesis but much less is known about the later events such as differentiation and the fate of odontogenic cells (Tompkins, 2006). This study revealed that PrP c was differentially expressed from two different stages of tooth development: before the differentiation of odontogenic cells (cap-staged 3rd molar germs) and after the differentiation and hard tissue formation (root formation-staged 2nd molar germs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much research on the molecular mechanisms responsible for initial odontogenesis but much less is known about the later events such as differentiation and the fate of odontogenic cells (Tompkins, 2006). This study revealed that PrP c was differentially expressed from two different stages of tooth development: before the differentiation of odontogenic cells (cap-staged 3rd molar germs) and after the differentiation and hard tissue formation (root formation-staged 2nd molar germs).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes are associated with early events such as patterning and morphogenesis of odontogenic cells (Cobourne and Sharpe, 2003;Miletich and Sharpe, 2004;Thesleff, 2006). Much less is known about molecules that are involved in the differentiation and phenotypic expression of dental follicular cells for periodontal ligament development as well as odontogenic cells for dental hard tissue formation (Tompkins, 2006). Many investigations of the cyto-differentiation of odontogenic cells have used in vitro or ex vivo culture systems and therefore, could not represent all in vivo phenomena for cell signaling (Jiang et al, 2010;Liu et al, 2013;Yasukawa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tooth development is the cumulative result of spatial and temporal interactions between different tissues, namely, of mesoderm and ectoderm origins (Sharpe, 2001;Tucker and Sharpe, 2004), and progresses through 4 widely recognized stages of tooth development: the bud, cap, bell, and crown stages. Complex and repeated signaling interactions determine the formation, position, and overall shape of tooth development (Tucker and Sharpe, 1999;Sharpe, 2001;Thesleff, 2003;Coudert et al, 2005;Honda et al, 2005;Tompkins, 2006;Kapadia et al, 2007;SalazarCiudad, 2008) (Fig. 1).…”
Section: Tooth Structure and Developmentmentioning
confidence: 99%
“…Much experimental work to this effect has shown that genetic regulators such as the Barx1 homeobox gene (Thomas and Sharpe, 1998;Ferguson et al, 2000;Miletich et al, 2005) are important for directing the formation and location of teeth from the tooth germ (Tucker and Sharpe, 2004;Mitsiadis and Smith, 2006). Several other genes, important to tooth morphogenesis and development, have also been identified (Thesleff and Åberg, 1999;Tucker and Sharpe, 1999;Fukumoto and Yamada, 2005;Ryoo and Wang, 2006;Tompkins, 2006;Foster et al, 2007;Hu and Simmer, 2007;Kapadia et al, 2007;Thesleff et al, 2007).…”
Section: Scaffold-free Regeneration Of the Toothmentioning
confidence: 99%
“…However, most studies examined the early tooth developmental events from initiation to the early bell stage, which precedes the formation of dental hard tissue. Accordingly, there are relatively few reports on the molecular events for terminal cytodifferentiation and maturation of dental hard tissues as well as the preparation of an eruption pathway (Tompkins, 2006). Moreover, in vitro tooth culture systems have been used in most studies on the differentiation of dental hard tissue cells and therefore, cannot represent precisely the events that take place in vivo (Unda et al, 2000).…”
mentioning
confidence: 99%